Regulation of astaxanthin accumulation in Phaffia rhodozyma under titanium dioxide and rapeseed oil stress by amino acid metabolism - Liu, Meizhen; Han, Tiantian; Luo, Lu; Zhang, Ying; Yuan, Gaofeng; Fang, Xubo; Dong, Keyu; Zhang, Jing; Chen, Xiaoe (Food chemistry, 2025)
This study aimed to identify effective strategies for the sustainable production of natural astaxanthin by Phaffia rhodozyma. The combination of titanium dioxide (TiO2) and rapeseed oil boosted astaxanthin production in P. rhodozyma PR106 to 47.31 mg/L, a 6.24-fold increase compared to the control. Meanwhile, the levels of phytoene, lycopene, and β-carotene decreased by 16.8 %, 17.4 %, and 4.0 %, respectively. Notably, TiO2 and rapeseed oil enhanced the activity of superoxide dismutase and catalase, lowering reactive oxygen species levels. The mechanisms underlying the enhanced astaxanthin production in PR106 involve significant changes in intracellular purine metabolism, ABC transporters, glycolysis, the TCA cycle, and amino acid metabolism induced by TiO2 and rapeseed oil stress. Finally, this study confirmed that amino acid metabolism (particularly involving succinic acid and valine) played a crucial regulatory role in the biosynthesis of astaxanthin. This research provides a robust theoretical foundation for the industrial development of natural astaxanthin. [Display omitted] •Dual stressors boost high astaxanthin yield in P. rhodozyma PR106 was identified.•TiO2 and rapeseed oil stress increased astaxanthin yield in PR106 by 6.24-fold.•TiO2 and rapeseed oil reduced ROS and improving the activity of SOD and CAT in PR106.•Amino acid regulates astaxanthin accumulation in PR106 under dual stress conditions.